37th Annual Maverick Rodeo July 4, 1960
This program is for the Cimarron Rodeo being held on July 4, 1960
Judges : Gene Hayward, Frank Burk, Ray H. Bryan, Sid Dennis, Jim Curtis, Toke Harp, Roy Cartwright, Dave Gillespie, Ed Springer, W.J. Gourley, Bill Heck, Les Davis, Sandy Valdez, Maggie Trujillo, Emmett Duke, Vance Lusk, Homer Bennett, Howard McDaniel, George Laumbah, Phil Newlin, Mike Hope, Bill Littrell, Max Maez Cimarron Maverick Club list of members on page 13 of the program
Master List Item # 18
File location is in the New Mexico File Cabinets
Keywords: General Kearny; Springer, Charles; Jackson, Edward; Schwartz, Rudolph; Knox, Bob; Jackson, Ed; Hutson, Russell; Lento, Rosso; Piper, Joe; Heck, Bill Jr; Brewster, Bill; Jeffers, Ed; Powell, Hubert; Ward, Zenas; Gourley, Joe; Wheatley, Caleb; Davis, Les; Rhea, Jack; Alpers, Bunny; Morrison, Don; Swinney, Bill; Hope, Mike; Cope, Bill; Ethell, Russell; Littrell, Bill; McDaniels, Howard; Nowlin, Phil; Piper, Joe; Parker, John; Arnello, Johnny; Grob Roy; Bowen, Ralph; Carter, Carl D; Maverick Club; Turtle Club; Charles Springer Cattle Company; Sangre De Cristo Company; J & J Mercantile company; Philmont Scout Ranch; Don Diego Hotel Cocktail Lounge; Li Lisio's; Ranch Bar; The Tribune Press; First National Bank; Interstate Lumber Mills; Nixon's Tire Service; Spur Bowling Lanes bowl; Spur Supper club; Cimarron Mercantile Company; Nixon's Incorporated; Colt Motor Hotel and Coffee shop; Bernard's Hardware; Cimarron Gas Company; Rubin's; R & R Shoe Store; Raton Daily Range; J.W.Leitzell Service Station; Modern Electric & Furniture; Raton Building Supply; U U Ranch